1999
DOI: 10.1002/(sici)1521-1878(199907)21:7<579::aid-bies6>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic trafficking of proteins: With or without Ran?

Abstract: Proteins and RNAs move between the nucleus and cytoplasm by translocation through nuclear pore complexes in the nuclear envelope. To do this, they require specific targeting signals, energy, and a cellular apparatus that catalyzes their transport. Several of the factors involved in nucleocytoplasmic trafficking of proteins have been identified and characterized in some detail. The emerging picture for nuclear transport proposes a central role for the small GTPase Ran and proteins with which it interacts. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 81 publications
1
24
0
1
Order By: Relevance
“…The soluble factors Ran and importin-b as well as the nucleoporin Nup153 are essential components of the classical nuclear import apparatus (reviewed in Stochaj and Rother, 11 Gö rlich and Kutay 12 and Kü nzler and Hurt 15 ). Importantly, hydrogen peroxide treatment of HeLa cells interferes with the formation of the Ran concentration gradient (Figure 2A, d; 2B).…”
Section: Oxidants Redistribute Nuclear Transport Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soluble factors Ran and importin-b as well as the nucleoporin Nup153 are essential components of the classical nuclear import apparatus (reviewed in Stochaj and Rother, 11 Gö rlich and Kutay 12 and Kü nzler and Hurt 15 ). Importantly, hydrogen peroxide treatment of HeLa cells interferes with the formation of the Ran concentration gradient (Figure 2A, d; 2B).…”
Section: Oxidants Redistribute Nuclear Transport Factorsmentioning
confidence: 99%
“…Like cytoplasmic transport factors, nucleoporins are involved in nucleocytoplasmic trafficking of proteins and RNA (reviewed in Stochaj and Rother, 11 Gö rlich and Kutay 12 and Kuersten et al 13 ). For instance, Nup153, a member of the FXFG family of nucleoporins, is located at the nuclear basket, where it participates in the termination of classical nuclear protein import.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown that deletion of a region encompassing the GATA-3 NLS region (aa 249 -311) prevents nuclear localization of the overexpressed protein (11). The affinity of the importin-␣-NLS interaction is a critical parameter in determining nuclear transport efficiency and may be influenced directly by phosphorylation (13,15,17).…”
mentioning
confidence: 99%
“…7). One of the most intriguing of these involves the movement of calmodulin across the nuclear pore (8 -10).…”
mentioning
confidence: 99%